The cause of an extreme sea surface warming in the midlatitude western North Pacific during 2012 summer - Li, Zhiyuan; Wu, Gangfeng; Xu, Chang; Zhao, Jing; Wang, Mengqiao; Sheng, Jie; Shen, Yi; Zhu, Xiao-Hua (Frontiers in Marine Science, 2024)
This study investigated an extreme sea surface warming in the midlatitude western North Pacific (MLWNP) during the summer of 2012. The 2012 extreme event was characterized by warm sea surface temperature anomaly (SSTA) extending from the East/Japan Sea to central North Pacific. The SSTA box-averaged over the MLWNP (130-180°E, 33-50°N) in 2012 ranked as the third warmest in recent four decades, which has caused intense marine heatwaves in this region. During the summer of 2012, a positive Indian Ocean Dipole event co-occurred with El Niño, favoring anomalous moisture transport between the two basins that caused enhanced convection in the South China and Philippine Seas and western-to-central subtropical Pacific. The enhanced convective activities triggered two meridional atmospheric Rossby wave trains to form strong atmospheric blocking highpressure systems in the MLWNP. This reduced the total cloud cover and surface wind speed, enhancing insolation and reducing the release of latent heat flux. In addition, the weakened wind strengthened the stratification and shoaled the mixed layer. As a result, the increased net heat flux into the ocean accompanied by a shallower mixed layer contributed to the upper ocean warming in the MLWNP. Meanwhile, the North Pacific was dominated by a negative phase of Pacific Decadal Oscillation (PDO), significantly contributing to warm SSTAs in the MLWNP in 2012. Consequently, the 2012 extreme warming in the MLWNP was the results of the combination of atmospheric Rossby waves and PDO. Our study highlighted the roles of high-frequency atmospheric teleconnection and low-frequency PDO in extreme sea surface warming in the MLWNP.